The Impact of Electronic Advertising on Consumer Purchasing Behaviour in Algeria - Assia BRAHIMI; Djamila KADRI (Management and Economics Review, 2025)
Through this study, we seek to identify the impact of electronic advertising on the purchasing behaviour of the Algerian consumer, and to reach the goal of the study, we designed a questionnaire and distributed it to a sample of 128 people via the Internet, and to process and analyse the data, we used the statistical processing programme SPSS v22. The results of the study confirmed the existence of a positive relationship between electronic advertising in its four dimensions (characteristics of electronic advertising, credibility of electronic advertising, incentives for electronic advertising, content of the advertising message) and the purchasing behaviour of the Algerian consumer.